Sediment model for natural and man-made channels using general regression neural network - Junaidah, Ariffin; Nurashikin, Ahmad Kamal; Muhamad Syahreen, Sa’adon; Mohd Nasir, Taib; Suhaimi, Abdul-Talib; Aminuddin, Abd-Ghani; Nor Azazi, Zakaria; Ahmad Shukri, Yahaya (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/